Development of psychopathology in deployed armed forces in relation to plasma GABA levels. (November 2016) - Schür, Remmelt R.; Boks, Marco P.; Geuze, Elbert; Prinsen, Hubertus C.; Verhoeven-Duif, Nanda M.; Joëls, Marian; Kahn, René S.; Vermetten, Eric; Vinkers, Christiaan H.
Highlights: Prospective changes in plasma GABA levels are related to the development of psychopathology (e.g. depressive and posttraumatic stress disorder symptoms) after military deployment. Baseline plasma GABA levels did not predict the development of psychopathology. Plasma GABA increase may constitute a compensatory mechanism for (post-deployment) psychopathology symptoms as GABA rises following the emergence of psychopathology symptoms. Abstract: The GABA system is pivotal for an adequate response to a stressful environment but has remained largely unexplored in this context. The present study investigated the relationship of prospectively measured plasma GABA levels with psychopathology symptoms in military deployed to Afghanistan at risk for developing psychopathology following trauma exposure during deployment, including posttraumatic stress disorder (PTSD) and major depressive disorder (MDD). Plasma GABA levels were measured in military personnel (N = 731) one month prior to deployment (T0), and one (T1) and six months (T2) after deployment using ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC–MS/MS). Mental health problems and depressive symptoms were measured with the Dutch revised Symptom Checklist (SCL-90) and PTSD symptoms with the Dutch Self-Rating Inventory for PTSD (SRIP). Six months after deployment increases in GABA concentrations were present in individuals who had developed mental health problems (T2: β = 0.06, p = 1.6 × 10 −2, T1: β = 4.7 × 10 −2, p = 0.13), depressive symptoms (T2: β = 0.29, p = 7.9 × 10 −3, T1: β = 0.23, p = 0.072) and PTSD symptoms at T2 (T2: β = 0.12, p = 4.3 × 10 −2, T1: β = 0.11, p = 0.13). Plasma GABA levels prior to and one month after deployment poorly predicted a high level of psychopathology symptoms either one or six months after deployment. The number of previous deployments, trauma experienced during deployment, childhood trauma, age and sex were not significantly associated with plasma GABA levels over time. Exclusion of subjects who either started or stopped smoking, alcohol or medication use between the three time points rendered the association of increasing GABA levels with the emergence of psychopathology symptoms more pronounced (mental health problems at T2: β = 0.09, p = 4.2 × 10 −3 ; depressive symptoms at T2: β = 0.35, p = 3.5 × 10 −3, PTSD symptoms at T2: β = 0.17, p = 1.7 × 10 −2 ). To our knowledge, this is the first study to provide prospective evidence that the development of psychopathology after military deployment is associated with increasing plasma GABA levels. Our finding that plasma GABA rises after the emergence of psychopathology symptoms suggests that GABA increase may constitute a compensatory mechanism and warrants further exploration of the GABA system as a potential target for treatment.